An overview of transboundary haze studies: the underlying causes and regional disputes on Southeast Asia region - Ku Yusof, Ku Mohd Kalkausar; Azid, Azman; Samsudin, Mohd Saiful; Jamalani, Mohd Asrul (Penerbit UTM Press, 2017)
Air pollution is now ranked as the ninth worst scenario globally and is expected to be the most serious global issue by the year 2050. The objective of this study is to get information regarding transboundary haze phenomenon blanketing the Southeast Asia that has been happened for decades ago. Various techniques such as qualitative and quantitative techniques have been applied to get the informative input detailed out by previous researchers. The finding shows that that the smoky haze occurred in the dry season, which at this point, the activities of cleaning and ground maintenance being carried out by Indonesian farmers. Indonesia is one of the countries drastically affected by deforestation process where their forest loss is 2% yr-1 which is equal to 1.9 million ha each year. The establishment of ASEAN in 2002 would be a turning point in addressing on more reliance on prevention and cooperation than establishing a liability regime or adopting legal instruments to protect the environment. However, the reflection of so-called ‘ASEAN Way', which preferred on non-interference in other states has inhibited the reliance on strong regional efforts in executing a more effective action in order to address and combat the transboundary haze pollution in Southeast Asia.